SCHOOL DROPOUT: A CASE STUDY IN TECHNICAL EDUCATION IN ADMINISTRATION AT ABC PAULITA (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
This article aims to analyze the phenomenon of school dropout in a high school technical course at the State Center for Technological Education Paula Souza. The general objective of the research was to understand intra- and extra-school causes declared by dropout students and the management team of the Technical Course in Administration of a State Technical School located in the ABC Paulista region. Methodologically, this case study used documentary sources, application of questionnaires and qualitative data collected in a discussion group with the managers of the researched unit. The results show that the main causes of school dropout are of extra-school nature, especially difficulties of reconciling work activities with studies, financial, personal and/or health problems. The most prominent intra-school causes were poorly motivating classes and the mismatch between the course requirements and the students background from their previous stages of schooling. It was observed that, despite the management team great concerns about the school dropout, the actions and strategies adopted by the school have been insufficient to control that phenomenon.Keywords: School droupout, Techinical-professional education, School management.